Development of thermodynamic conceptual evaluation - Talaeb P. (2014)
This research aims to develop a test for assessing student understanding of fundamental principles in thermodynamics. Misconceptions found from previous physics education research were used to develop the test. Its topics include heat and temperature, the zeroth and the first law of thermodynamics, and the thermodynamics processes. The content validity was analyzed by three physics experts. Then the test was administered to freshmen, sophomores and juniors majored in physics in order to determine item difficulties and item discrimination of the test. A few items were eliminated from the test. Finally, the test will be administered to students taking Physics I course in order to evaluate the effectiveness of Interactive Lecture Demonstrations that will be used for the first time at Chiang Mai University. © 2010 American Institute of Physics.